2007
DOI: 10.1371/journal.pmed.0040309
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Artemisinin-Based Combination Therapy and Insecticide-Treated Nets on Malaria Burden in Zanzibar

Abstract: BackgroundThe Roll Back Malaria strategy recommends a combination of interventions for malaria control. Zanzibar implemented artemisinin-based combination therapy (ACT) for uncomplicated malaria in late 2003 and long-lasting insecticidal nets (LLINs) from early 2006. ACT is provided free of charge to all malaria patients, while LLINs are distributed free to children under age 5 y (“under five”) and pregnant women. We investigated temporal trends in Plasmodium falciparum prevalence and malaria-related health pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
462
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 539 publications
(492 citation statements)
references
References 10 publications
20
462
2
Order By: Relevance
“…eradication | migration | network analysis | imported malaria | community detection S ignificant progress is being made in reducing the morbidity and mortality attributed to malaria globally (1)(2)(3)(4)(5)(6)(7)(8)(9)(10), encouraging the Global Malaria Action Plan (GMAP) (11) to articulate a long-term vision for malaria eradication through shorter-term local efforts to eliminate malaria. A total of 34 of the 107 malaria endemic countries have declared they have a national policy for malaria elimination or are pursuing spatially progressive elimination within their borders (11)(12)(13).…”
mentioning
confidence: 99%
“…eradication | migration | network analysis | imported malaria | community detection S ignificant progress is being made in reducing the morbidity and mortality attributed to malaria globally (1)(2)(3)(4)(5)(6)(7)(8)(9)(10), encouraging the Global Malaria Action Plan (GMAP) (11) to articulate a long-term vision for malaria eradication through shorter-term local efforts to eliminate malaria. A total of 34 of the 107 malaria endemic countries have declared they have a national policy for malaria elimination or are pursuing spatially progressive elimination within their borders (11)(12)(13).…”
mentioning
confidence: 99%
“…Similarly, pregnant women A recent study in Zanzibar showed that, following deployment of antimalarial combined therapy, malariaassociated morbidity and mortality decreased dramatically: crude under-five mortality decreased by 52% while infant and child mortality declined by 33% and 71%, respectively. 10 Similarly, in Eritrea, following implementation of multiple intervention coverage, malaria morbidity and case fatality fell by 84% and 40%, respectively.…”
Section: Previous Year Latest Yearmentioning
confidence: 99%
“…8 In the past few years, African countries, such as Tanzania, Sao Tome and Principe, Eritrea, and Rwanda, where malaria is endemic, have provided high-risk populations with effective mosquito control intervention and access to artemisinin-based combination therapies (ACTs). [9][10][11] Additionally, small elimination campaigns utilizing frequent insecticide spraying in houses and rounds of mass treatment were undertaken in Nigeria, under the auspices of the Garki project 12 and on the Kenyan/Tanzanian border, termed the Pare-Taveta project. 8,13 These projects entailed the combination of frequent insecticide spraying in houses to reduce vector populations and mass treatment to reduce the human infectious reservoir.…”
Section: Current Status Of Malaria Control Eradication and Eliminationmentioning
confidence: 99%